Grazing Molecule Excitation as a Tool to Analyse the Amino Acid Sequence in Oligopeptides. (29th October 2011) - Jungclas, H.; Schmidt, L.; Komarov, V. V.; Popova, A. M.
Abstract : A novel mass spectrometric method to analyse the sequence of amino acid residues in oligopeptides is proposed. Amino acid residues in peptide molecules contain chain-like structures of identical CH dipoles (IR antennas), which acquire IR energy quanta by interaction with periodic Coulomb fields and accumulate vibration excitation energy. This can subsequently lead to the dissociation of specific trap bonds inside the peptide molecule. Such excitation and dissociation processes are assumed to occur when peptide ions graze at atomic distance along a set of screened charges on a surface. These processes of grazing molecule excitation (GME) and dissociation (GMD) were applied to analyse sequences of oligopeptides by using TOF mass spectrometry. At specific grazing velocities the experimental fragment ion spectra of oligopeptides must contain a peak of high abundance corresponding to the N-terminal amino acid. This specific property of GMD offers the possibility to determine the amino acid sequence of oligopeptides.